FEATURES OF THE INTERPRETATION OF THE RESULTS OF DNA EXAMINATION RESEARCH - Kamoliddinova , Feruza Kamoliddin qizi; Akbarov , Navro‘z Jahongir o‘g‘li (Educational Research in Universal Sciences, 2023)
The article emphasizes the importance of understanding the limitations of DNA analysis, including the possibility of false positives and false negatives, as well as the potential for errors in sample collection and analysis. It also highlights the need for caution when interpreting mixed DNA profiles, which can be particularly challenging to analyze and may require advanced statistical methods. The article discusses various factors that can affect the interpretation of DNA evidence, including the quality and quantity of the DNA sample, the presence of DNA from multiple contributors, and the use of different DNA analysis techniques. It also explores the impact of population genetics on the interpretation of DNA evidence, including the importance of using appropriate reference databases to calculate match probabilities.